A Research on the Academic Improvement Effects of Extracurricular Mathematics Tutoring for Chinese High School Students (Asian Education Studies, 2022)
To examine the academic enhancement effects of extracurricular tutoring in mathematics at the high school level, 439 questionnaires were distributed in the second year of senior high school to collect information on the number of participants in different types of tutoring and the grade level mathematics scores before and after tutoring, and the data obtained were analyzed for differences using SPSS software. The results showed that (1) extracurricular tutoring in mathematics for high school students can improve students' academic performance, but the improvement effects of different types of extracurricular tutoring have significant differences. (2) Among students of different levels, the degree of improvement in the group of mathematics students with difficulties was significantly higher than that in the group of intermediate and superior students; the degree of improvement within the group of intermediate students was seriously polarized. Therefore, the academic improvement effect of extracurricular tutoring in mathematics varies depending on the type of tutoring, students with learning difficulties in mathematics should consider choosing appropriate extracurricular tutoring in mathematics, and mathematics teachers should strengthen personalized guidance for students.